2013
DOI: 10.5301/hipint.5000054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations in Ten Patients with Asymptomatic Metal-on-Metal Hip Arthroplasty with Very High Cobalt Levels

Abstract: Reports of adverse reactions to metal particle debris with metal-on-metal (MoM) hip arthroplasty have increased recently. Apart from the formation of pseudotumours and higher revision rates, another major cause for concern are the systemic effects of metal ions. Several effects of elevated systemic cobalt ions have been reported (e.g., myocardial and neurological effects, hypothyroidism). All 643 patients who underwent a stemmed large head MoM total hip replacement in our clinic were screened with repeated who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Although the manuscript by Megaterio et al 15 did not include blood cobalt levels, we elected to include it because it was the first case report of arthroprosthetic cobaltism and the patient reportedly had significant increases in blood and urine cobalt levels. In total, we included 22 manuscripts, 1416,2341 one of which reported 3 patients, 37 three of which reported 2 patients, 32,38,39 and 2 occasions where descriptions of the same patient were reported twice. 29,34,40,41 This led to results for 25 unique patients.…”
Section: Methodsmentioning
confidence: 99%
“…Although the manuscript by Megaterio et al 15 did not include blood cobalt levels, we elected to include it because it was the first case report of arthroprosthetic cobaltism and the patient reportedly had significant increases in blood and urine cobalt levels. In total, we included 22 manuscripts, 1416,2341 one of which reported 3 patients, 37 three of which reported 2 patients, 32,38,39 and 2 occasions where descriptions of the same patient were reported twice. 29,34,40,41 This led to results for 25 unique patients.…”
Section: Methodsmentioning
confidence: 99%
“…They therfore conclude that a large revision is not indicated in asymptomatic patients with highly elevated blood metal ions. 22 Christian et al demonstrated that the toxicological weight of evidence suggests that MoM hip implants are unlikely to be associated with an increased risk of systemic cancers, which is consistent with published and ongoing epidemiologic studies investigating the relationship between elevated Co and Cr serum levels and increase in systemic cancers. 23 Paustenbach et al, who examined the connection between Co serum concentrations and adverse biological effects, concluded that only under very unusual circumstances biologically important systemic effects might occur in MoM hip implant patients with Co serum concentrations of less than 300 ppb.…”
Section: Discussionmentioning
confidence: 53%
“…Chen et al [38] were able to show discrete changes in some immune markers, but no impairment of liver or kidney function, after a rather short follow-up of two years following MoM large head hip arthroplasty. Likewise, the study of Van Lingen et al [39] did not find any organ damage in a group of 10 patients with significantly elevated cobalt levels (mean 46.8 µg/l, 18-153 µg/l) from a total cohort 643 of patients 4 years after MoM large-head hip arthroplasty. In summary, while isolated cases of problem implants and, above all, metal head use in revision surgery for previous ceramic fracture run the risk of cobalt-related organ damage, this will not impact most patientsespecially those with clinically well-functioning MoM implants.…”
Section: Systemic Toxicitymentioning
confidence: 86%